Improvement of practical control method for positioning systems in the presence of actuator saturation by incorporating fuzzy anti-reset windup - Wahyudi, Martono; Ibrahim, Tarig. F.; Albagul, Abdulgani; kuswadi, S.; Salami, Momoh Jimoh Emiyoka (2004)
The positioning systems generally need a good controller to achieve high accuracy, fast response and robustness. In addition, ease of controller design and simplicity of controller structure are very important for practical application. For satisfying these requirements, NCTF (nominal characteristic trajectory following controller) has been proposed as a practical PTP positioning control. However, the effect of actuator saturation can not be completely compensated due to integrator windup when the object parameters vary. This paper presents a method to improve the NCTF controller for overcoming the problem of integrator windup by adopting a fuzzy anti-windup. The improved NCTF controller is evaluated through simulation using a rotary positioning system. The results show that the improved NCTF controller is effective to compensate the effect of integrator windup.